2020
DOI: 10.1111/1759-7714.13702
|View full text |Cite|
|
Sign up to set email alerts
|

Prognostic impact of micropapillary component in patients with node‐negative subcentimeter lung adenocarcinoma: A Chinese cohort study

Abstract: Background: In this study, we investigated the prognostic significance of a micropapillary (MP) component in patients with subcentimeter lung adenocarcinoma. Methods: A total of 311 patients with subcentimeter lung adenocarcinoma who underwent surgical resection between January 2009 to December 2012 from seven medical centers were included. Recurrence-free survival (RFS) and overall survival (OS) were analyzed. Results: The five-year RFS was 79.8% in 97 (97/311, 31%) cases of adenocarcinoma with a MP component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
2
7
0
Order By: Relevance
“…Yao et al. ( 19 ) found that patients with subcentimetre lung adenocarcinoma with micropapillary components had a poor prognosis, and wedge resection was associated with a higher risk of recurrence than anatomic lung resection (segmentectomy and lobectomy), which was similar to our results.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Yao et al. ( 19 ) found that patients with subcentimetre lung adenocarcinoma with micropapillary components had a poor prognosis, and wedge resection was associated with a higher risk of recurrence than anatomic lung resection (segmentectomy and lobectomy), which was similar to our results.…”
Section: Discussionsupporting
confidence: 91%
“…When the micropapillary histological components were more than 5%, the survival rate of lobectomy was higher, while in the patients with micropapillary histological components lower than 5%, there was no significant difference in survival rate after different surgical methods. Yao et al (19) found that patients with subcentimetre lung adenocarcinoma with micropapillary components had a poor prognosis, and wedge resection was associated with a higher risk of recurrence than anatomic lung resection (segmentectomy and lobectomy), which was similar to our results.…”
Section: Figuresupporting
confidence: 91%
“…Several previous studies have determined that the presence of at least a 5% MPC is inversely associated with survival ( 21 , 22 ). Patients with sub-centimeter LA, with a ≥ 5% MPC, treated with a wedge resection, had a higher risk of recurrence ( 23 ). However, a MPC < 5% has also been determined to have a significant impact on OS ( 22 ).…”
Section: Discussionmentioning
confidence: 99%
“… 28 Chen et al had showed wedge resection was associated with higher risk of recurrence compared with anatomic resection for sub‐centimeter lung adenocarcinoma with a micropapillary component of 5% or greater in a cohort 311 patients. 29 Contrarily, unlike micropapillary and solid predominant subtypes, patients with adenocarcinoma ≤1 cm with micropapillary and/or solid component (not predominant) treated with wedge resection did not show inferior RFS and OS compared with anatomical resection ( p = 0.58) in our study. It is noteworthy that the wedge resections in our cohort had a resection margin more than 1 cm, which might suggest the local infiltration for invasive adenocarcinoma ≤1 cm with micropapillary and solid component (not predominant) is less than 1 cm.…”
Section: Discussionmentioning
confidence: 40%
“…Lee et al had reported that even a small component of micropapillary pattern will have a significant prognostic impact on OS 28 . Chen et al had showed wedge resection was associated with higher risk of recurrence compared with anatomic resection for sub‐centimeter lung adenocarcinoma with a micropapillary component of 5% or greater in a cohort 311 patients 29 . Contrarily, unlike micropapillary and solid predominant subtypes, patients with adenocarcinoma ≤1 cm with micropapillary and/or solid component (not predominant) treated with wedge resection did not show inferior RFS and OS compared with anatomical resection ( p = 0.58) in our study.…”
Section: Discussionmentioning
confidence: 99%